Simulation of small-scale waste biomass gasification integrated power production: a comparative performance analysis for timber and wood waste - Sahar Safarian; Runar Unnthorsson; Christiaan Richter (International Journal of Applied Power Engineering (IJAPE), 2020)
A simulation model for integrated waste biomass gasification with cogeneration heat and power has been developed using Aspen Plus. The model can be used as a predictive tool for optimization of the gasifier performance. The system has been modeled in four stages. Firstly, moisture content of biomass is reduced. Secondly biomass is decomposed into its elements by specifying yield distribution. Then gasification reactions have been modeled using Gibbs free energy minimization approach. Finally, power is generated through the internal combustion engine as well as heat recovery system generator. In simulation study, the operating parameters like temperature, equivalence ratio (ER) and biomass moisture content are varied over wide range and their effect on syngas composition, low heating value (LHV) and electrical efficiency (EE) are investigated. Overally, increasing temperature and decreasing ER and MC lead to improvement of the gasification performance. However, for maximum electrical efficiency, it is important to find the optimal values of operating conditions.The optimum temperature, ER and MC of the down draft gasifier for timber and wood waste are 800 ̊C, 0.2- 0.3 and 5%. At such optimum conditions, CO and H2 reach to the highest production and LHV and EE are around 7.064 MJ Nm-3 and 45%, respectively.